Pengaruh Penggunaan Fiksasi Masker Paru Terhadap Ketepatan Terget Penyinaran Pada Kanker Paru Teknik Intensity Modulated Radiation Therapy (IMRT) Di Departemen Onkologi Radiasi Rumah Sakit Umum Jakarta - Mohd Alimin; Ni Putu Rita Jeniyanti (Pusat Riset dan Inovasi Nasional, 2024)
The Effect Of Use Of Lung Mask Fixation On The Accuracy Of Targeted Irradiation In Lung Cancer Intensity Modulated Radiation Therapy (Imrt) Technique In The Department Of Radiation Oncology, Jakarta General Hospital. Lung cancer is the uncontrolled growth of abnormal cells in one or both lungs. While normal cells in the lungs usually develop and reproduce to form healthy lung tissue, these abnormal cells actually reproduce more quickly and are never able to become normal lung tissue. As a result, lumps of cancer cells are formed, which are often referred to as tumors. (4) Radiotherapy is a form of therapy that has been proven to be useful in treating cancer. The aim of radiotherapy is to provide safe, accurate and efficient radiation doses to treat various types of cancer and also non-malignant disorders (7). Carrying out radiotherapy for lung cancer involves the use of immobilization devices, one of which is a thermoplastic mask. This mask functions to reduce the patient's body movements, including movements caused by breathing (9). Verification is a critical stage in the radiotherapy process. The purpose of this verification is to ensure that there are no significant differences in the exposure carried out (14). Giving the right dose of radiotherapy radiation is very necessary to achieve successful therapeutic treatment. The accuracy of dosing and the accuracy of the patient's position influence the dose distribution that will be received by the patient. This verification is based on the International Atomic Energy Agency (IAEA) Human Health Series No. 31 of 2016 with a displacement value of 0.3cm (15). EPID (Electronic Portal Imaging Device) is an additional device connected to the LINAC (Linear Accelerator) radiotherapy device. EPID functions as a verification tool for radiation dose and geometry which is very important in the radiotherapy process (16). The accuracy of the patient's position during radiation treatment greatly influences the accuracy of the IMRT technique. Before irradiation, verification is carried out using an EPID (Electronic Portal Imaging Device) to ensure the correct target position on the tumor. This helps measure the x, y, and z axis coordinates along the radiation area before the radiation procedure begins.